Making Animated Videos With The Canva Application As An Effort To Increase Student Motivation - Syaharuddin Syaharuddin; Rusmaniah Rusmaniah; Nursahid Nursahid; Muhammad Risalan Uzhma; M. Ridha Ilhami (Universitas Lambung Mangkurat, 2023)
One of the efforts made in increasing student learning motivation is by making fun learning innovations. Then by using learning media based on technology. So that in this service there will be skills training in making smartphone-based learning media with the Canva application. This training was conducted in partnership with SMP Negeri 13 Banjarmasin. The method used in this activity is the lecture and practice method. The lecture method is carried out to convey the advantages of using the Canva application, while the practical method is used to provide opportunities for teachers to practice making animated video learning media. The purpose of its implementation is to provide innovation to teachers so that students are not bored in learning and make it easier for students to understand the material.